Pawnshop Digital Service Quality and it’s Implication on Customer Satisfaction at PT Pegadaian (Persero) Pondok Labu Branch - Aziz Setyawan (Jurnal Indonesia Sosial Sains, 2022)
In the current era, services delivered through digital channels make up the majority of business transactions compared to those carried out through traditional channels such as branch offices. Starting with the theme “DigitalisMe”, Pegadaian launched a digital-based service called Pegadaian Digital. This study aims to empirically explore the service quality of Pegadaian Digital and their impact on customer satisfaction at PT Pegadaian (Persero) Pondok Labu Branch. This is a quantitative research, and the sample in this study amounted to 160 customers who are users of Pegadaian Digital services. The data collection process uses google forms and scanned barcodes that are distributed in each unit of the Pegadaian Pondok Labu Branch. The data were analyzed using the Partial Least Square (PLS) method, and the results show that: (1) Reliability has an effect on customer satisfaction (2) Efficiency has no effect on customer satisfaction (3) Security has no effect on customer satisfaction (4) Responsiveness has no effect on customer satisfaction (5) Web design has no effect on customer satisfaction.